Pretrauma Center Red Blood Cell Transfusion Is Associated With Reduced Mortality and Coagulopathy in Severely Injured Patients With Blunt Trauma. Issue 5 (May 2015) - Brown, Joshua B.; Cohen, Mitchell J.; Minei, Joseph P.; Maier, Ronald V.; West, Michaela A.; Billiar, Timothy R.; Peitzman, Andrew B.; Moore, Ernest E.; Cuschieri, Joseph; Sperry, Jason L.
Abstract : Objective: To evaluate the association of pretrauma center (PTC) red blood cell (RBC) transfusion with outcomes in severely injured patients. Background: Hemorrhage remains a major driver of mortality. Little evidence exists supporting PTC interventions to mitigate this. Methods: Blunt injured patients in shock arriving at a trauma center within 2 hours of injury were included from the Glue Grant database. Subjects were dichotomized by PTC RBC transfusion. Outcomes included 24-hour mortality, 30-day mortality, and trauma-induced coagulopathy [(TIC), admission international normalized ratio >1.5]. Cox regression and logistic regression determined the association of PTC RBC transfusion with outcomes. To address baseline differences, propensity score matching was used. Results: Of 1415 subjects, 50 received PTC RBC transfusion. Demographics and injury severity score were similar. The PTC RBC group received 1.3 units of RBCs (median), and 52% were scene transports. PTC RBC transfusion was associated with a 95% reduction in odds of 24-hour mortality [odds ratio (OR) = 0.05; 95% confidence interval (CI), 0.01–0.48; P < 0.01], 64% reduction in the risk of 30-day mortality [hazard ratio = 0.36; 95% CI, 0.15–0.83; P = 0.02], and 88% reduction in odds of TIC (OR = 0.12; 95% CI, 0.02–0.79; P = 0.03). The matched cohort included 113 subjects (31% PTC RBC group). Baseline characteristics were similar. PTC RBC transfusion was associated with a 98% reduction in odds of 24-hour mortality (OR = 0.02; 95% CI, 0.01–0.69; P = 0.04), 88% reduction in the risk of 30-day mortality (hazard ratio = 0.12; 95% CI, 0.03–0.61; P = 0.01), and 99% reduction in odds of TIC (OR = 0.01; 95% CI, 0.01–0.95; P = 0.05). Conclusions: PTC RBC administration was associated with a lower risk of 24-hour mortality, 30-day mortality, and TIC in severely injured patients with blunt trauma, warranting further prospective study. Abstract : No prior studies have compared outcomes in patients receiving pretrauma center (PTC) red blood cell (RBC) transfusion for trauma. Regression and propensity score matching were used to evaluate outcomes in blunt injured patients undergoing PTC RBC transfusion. PTC RBC transfusion was associated with a reduced risk of 24-hour mortality, 30-day mortality, and coagulopathy, warranting further study.